2014 IEEE 80th Vehicular Technology Conference (VTC2014-Fall) 2014
DOI: 10.1109/vtcfall.2014.6966077
|View full text |Cite
|
Sign up to set email alerts
|

On Buffer-Assisted Opportunistic Routing Relying on Linear Transmission Activation Probability Space Partitioning for Relay-Aided Networks

Abstract: Abstract-In this paper buffer-aided Opportunistic Routing (OR) was designed with the aid of the novel concept of linear Transmission Activation Probability Space (TAPS) partitioning invoked for relayassisted networks, which combines the benefits of both OR [1] and of buffer-aided transmissions [2]. More specifically, a packet may be transmitted from the Source Node (SN) to the Destination Node (DN) either directly or indirectly via one of the M Relay Nodes (RNs), depending on the instantaneous channel qualitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…which can be substituted into (13) in order to arrive at the exact OP for an arbitrary buffer size B as follows:…”
Section: P B=0mentioning
confidence: 99%
See 1 more Smart Citation
“…which can be substituted into (13) in order to arrive at the exact OP for an arbitrary buffer size B as follows:…”
Section: P B=0mentioning
confidence: 99%
“…On the other hand, the early contributions of the link‐activation design in buffer‐aided relaying mainly relied on a CQ of SNR, where the link having the maximum SNR was activated [2]. Recently, Dong et al [3, 12, 13] proposed the concept of transmission activation probability space (TAPS), where they found that a linear TAPS is sub‐optimal and hence proposed novel link‐activation protocols relying on a carefully‐designed non‐linear TAPS. Furthermore, in order to support the practical employment of the link‐activation protocols, the authors of [7, 11] proposed MAC layer protocols for buffer‐aided multi‐hop networks.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of TAPS was firstly introduced in our previous papers [22][23][24]. Although we proposed and applied the TAPS concept in several scenarios, the optimality of TAPS has not been formally shown.…”
Section: Review Of Taps and Proof Its Optimalitymentioning
confidence: 99%
“…The original concept of 'State' and MSTM were proposed in the context of buffer-aided systems in [5,13,[23][24][25]. Upon assuming that the buffer size of the RN is B packets, its state is defined as S b = b, when b packets are stored in the RN.…”
Section: Optimization Of the Link Activation Under A Delay-constrmentioning
confidence: 99%